2020
DOI: 10.31083/j.ceog.2020.04.5428
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rhodiola rosea root extract on stress-induced ovarian damage, infertility and reproductive disorders in female rats

Abstract: The aim of the study was to examine the possible effect of Rhodiola rosea root extract (RRE) on ovarian damage, infertility (IF), delay in conception (DC), decrease in the number of offspring (NO) in female rats that have been stressed with compulsory immobilization method (CIM) and on retardation of intrauterine physical development (IPD) in offspring. Materials and methods: Female Albino Wistar rats were divided like: healthy (HG), stress-induced control (SC), and stress + 50 mg/kg RRE (S + REG) groups inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
(72 reference statements)
0
0
0
Order By: Relevance
“…It was revealed in the study of Kadioglu et al that the stress induced by the forced immobilization method causes widespread congestion, hemorrhage, accumulation of fluid, and inflammatory infiltration in the subcapsular area in the ovaries. Infertility, delay in achieving pregnancy, decrease in the number of offspring, and intrauterine physical developmental retardation were found in the animal group with these histopathological signs 9 . The stress induced by the FIM has led to oxidative and inflammatory damage in the ovarian tissue of animals, sterility, and delay in achieving pregnancy.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It was revealed in the study of Kadioglu et al that the stress induced by the forced immobilization method causes widespread congestion, hemorrhage, accumulation of fluid, and inflammatory infiltration in the subcapsular area in the ovaries. Infertility, delay in achieving pregnancy, decrease in the number of offspring, and intrauterine physical developmental retardation were found in the animal group with these histopathological signs 9 . The stress induced by the FIM has led to oxidative and inflammatory damage in the ovarian tissue of animals, sterility, and delay in achieving pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…It is known that pro-inflammatory cytokine production plays a role in parallel with excessive oxidant production in the pathogenesis of ovarian damage, infertility, and delay in achieving pregnancy that develops due to stress and other factors 9,24 . Our results, accordingly, showed that TNF-α, L-1β and IL-6 levels increased in the ovarian tissue of animals with infertility and delay in achieving pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations